The Compulsory Immunization and Its Exemptions from the Perspective of the Police Power - Lyufan BAO (Yixue yu zhexue)
In the U.S., affairs relating to the compulsory immunization are mainly regulated by state police powers. Since the Jacobson case, the government's power to require citizens to be vaccinated has been consistently affirmed by the courts. Although skepticism surrounding this authority has not shaken the foundation of the compulsory immunization system, it has not transformed into a universal vaccination mandate. Immunization exemptions, as an institutional exception to compulsory immunization, not only bridge the gap between government compulsion and individual autonomy but also ensure the flexibility of the system. In China, laws similarly empower the government to establish vaccination plans. However, under the absolute compulsory immunization requirement, introducing the vaccination exemption may be an effective way to balance individual freedom and public interest.